Chile : Proposal for an Arrangement Under the Short-Term Liquidity Line-Press Release; Staff Report; and Statement by the Executive Director for Chile. (IMF Staff Country Reports; Country Report ;, 2022)
The Chilean economy has rapidly recovered from the fallout of the Covid-19 pandemic, thanks to an impressive vaccination campaign and effective policy support. The authorities will continue leveraging on Chile's very strong fundamentals and policy frameworks to safeguard the recovery, preserve macroeconomic stability, and boost inclusive and green growth.